The importance of homophile, strong ties, and social structures for female entrepreneurship in India - Dr. Swaminatha Sing; Hemaia Venkatara* (Al-Qanṭara, 2022)
The literature on women's entrepreneurship has significantly improved our understanding of the significance of focusing on women's contextual embeddedness for entrepreneurial activity. Our study uses a mixed-embeddedness perspective to explain how the multiple layers of women's embeddedness, particularly within the household-family and microcredit groups, enable or constrain women's microbusiness ownership in rural south India. Our study found that not all characteristics of women's household-family and microcredit group play a role in women's micro-business ownership by collecting and analysing data from over 9,800 women belonging to 649 microcredit groups in a region of south India. Women appear to rely on a limited number of capital resources related to the household-family, i.e. the home. Keywords- Women’s entrepreneurship, mixed-embeddedness, quantitative, multi-level, microcredit, India